2018
DOI: 10.1101/402180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basolateral localization of MMP14 drives apicobasal polarity change during EMT independently of its catalytic activity

Abstract: The transmembrane Matrix Metalloproteinase MMP14/MT1-MMP is known to promote cell migration by cleavage of the extracellular matrix. To initiate migration, epithelial cells need to gain mesenchymal attributes. They reduce cell-cell junctions and apicobasal polarity and gain migratory capabilities. This process is named epithelial-mesenchymal transition (EMT).MMP14's implication in EMT is still ill-defined. We used chick neural crest (NC) cells as a model to explore the function of MMP14 in physiological EMT. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
3
0
2
Order By: Relevance
“…These phenotypes, which are associated with defects in the ontogeny of cranial NCC derivatives, suggest that MMP14 is able to compensate for the loss of MMP16 in the mutant such that only the double KO yielded craniofacial defects. Notably, ours and others recent studies reported that MMP14 and MMP16 participate in executing NCC migration in Xenopus laevis and chick, respectively . Hence, MMP14 and MMP16 seem to also be necessary for multiple stages of NCC development, similar to MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These phenotypes, which are associated with defects in the ontogeny of cranial NCC derivatives, suggest that MMP14 is able to compensate for the loss of MMP16 in the mutant such that only the double KO yielded craniofacial defects. Notably, ours and others recent studies reported that MMP14 and MMP16 participate in executing NCC migration in Xenopus laevis and chick, respectively . Hence, MMP14 and MMP16 seem to also be necessary for multiple stages of NCC development, similar to MMP2 and MMP9.…”
Section: Discussionmentioning
confidence: 48%
“…Notably, ours and others recent studies reported that MMP14 and MMP16 participate in executing NCC migration in Xenopus laevis and chick, respectively. 44,82,83 Hence, MMP14 and MMP16 seem to also be necessary for multiple stages of NCC development, similar to MMP2 and MMP9. Future studies will be required to elucidate how these subgroups of MMPs cooperate in the regulation of NCC migration in different types of embryos.…”
Section: Discussionmentioning
confidence: 92%
“…In Xenopus embryos, the Smad-interacting protein-1 (Sip-1)-known to repress E-Cad expression in cancer cells-is required for NCCs to complete EMT, disperse, and migrate out from dorsal positions of the neural tube (Rogers et al, 2013). The metalloproteinase MMP14, through control of both E-Cad and N-Cad, also regulates both EMT and migration (Garmon et al, 2018), at least in part through a change in apicobasal polarity (Andrieu et al, 2018). Transcription factors such as Ets (Theveneau et al, 2007) and the Wnt signaling effector Axud1 (Simoes-Costa et al, 2015) are also required for the successful separation of NCCs from the neuroepithelium, with the latter additionally playing an earlier role in NCC specification.…”
Section: Discussionmentioning
confidence: 99%
“…De hecho, nuestro estudio muestra una distribución polarizada de la MMP-14 en los dobletes celulares de ratones wild type, mostrando que la deficiencia de esta proteasa puede interferir en la simetría celular. En concordancia con este dato, durante la transición epitelio-mesénquima, la MMP-14 se asociada a la integrina-β1 localizada en el lado apical de la célula, trasladándose al lado basal durante la migración celular al interaccionar con la integrina-β3, proceso mediado por el dominio extracelular de la MMP-14, independientemente de su actividad catalítica290 .El hecho de que las MMPs, y en concreto la MMP-14, participen en la polaridad celular podría explicar además la distribución asimétrica de distintos componentes de la MEC durante las divisiones de las células satélite. Por ejemplo, la presencia de laminina-a1 en la lámina basal del…”
unclassified
“…También es necesario considerar la complejidad de la MMP-14, que además de procesar proteínas estructurales de la MEC puede degradar moléculas de señalización pro-fibróticas como TNF-b, moléculas de la superficie celular como integrinas y quimoquinas o factores de crecimiento como FGF315,329 , que pueden afectar directamente a las células satélite o indirectamente, afectando a otras células que conforman su nicho y que participan en la regeneración muscular22 . Además, la MMP-14 no sólo media procesos celulares a través de su función proteolítica, pudiendo actuar también sobre distintas rutas de señalización a través de su cola citoplasmática194 o su dominio extracelular290 .…”
unclassified